2011
DOI: 10.2298/sarh1108536m
|View full text |Cite
|
Sign up to set email alerts
|

Silicotuberculosis and silicosis as occupational diseases: Report of two cases

Abstract: In low-income countries, new cases of silicosis and associated lung cancer, chronic obstructive pulmonary disease and tuberculosis are likely to be seen for decades because necessary reduction of silica use will take time to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Our studies revealed that both pathological characteristic and bacteriological indexes in different stages of silicosis rats with tuberculosis were similar to that of corresponding clinical patients, 15 which confirmed the reasonableness of it for study. In the future, such a model will be used to explore the specific pathogenesis of silicosis tuberculosis and provide more theoretical support for the treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Our studies revealed that both pathological characteristic and bacteriological indexes in different stages of silicosis rats with tuberculosis were similar to that of corresponding clinical patients, 15 which confirmed the reasonableness of it for study. In the future, such a model will be used to explore the specific pathogenesis of silicosis tuberculosis and provide more theoretical support for the treatment.…”
Section: Discussionsupporting
confidence: 77%
“…In patients with silicosis, it is extremely important to exclude the coexistence of active tuberculosis. However, the diagnosis of active tuberculosis superimposed on silicosis can be very difficult, because the clinical manifestations can be benign and the radiological alterations can be indistinguishable from those resulting from the preexisting silicosis [ 17 ]. Therefore, in cases of clinical suspicion of concomitant active tuberculosis, an appropriate additional investiga¬tion should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Both the patients presented diffuse lung fibrosis, small nodular opacities, and homogenous calcifications noted predominantly in the upper and middle lobes. 15 The other case study published by Mulliez et al, 16 reported 65-year-old male patient with silicotuberculosis developed broncholithiasis. A case of silicotuberculosis in a 76-yearold woman who has exposure of 3 years to silica dust was complicated by broncholithiasis and oesophagobronchial fistula and relapsed TB even on 9 months of anti-TB treatment.…”
Section: Discussionmentioning
confidence: 93%